Audiobooks for Assisting EFL Students in Reading Independently - Muhammad Riswanda Imawan; Ashadi Ashadi (Yayasan Visi Intan Permata, 2019)
Scholars and practitioners have done much research in developing EFL students' reading skill so that they can recall the main points of a text, answer literal and/or inferential questions, and even complete the actual reading of the text. Yet, those mainly have to involve the presence of a teacher or tutor for monitoring whereas students should be trained to be independent in reading. By reviewing related literature, this article is suggesting to use ‘Audiobook' to assist EFL students in reading independently. This article describes how the teaching of reading for EFL students, and how audiobooks can contribute to it. This all finally come with a conclusion that audiobook definitely can assist EFL in students in reading independently that later will supportively develop their reading skill and language competence besides their listening skill itself.